O formante do cantor e os ajustes laríngeos e supralaríngeos em cantores barítonos: uma investigação acústica e fibronasolaringoscópica - Cristina de Souza Gusmão (2014)
Objective: Identification of the laryngeal and supralaryngeal adjustments of singers formant in baritones during utterance of singing voice. Methods: Twelve baritones were evaluated through acoustic assessment and imaging in the fibronasalaringoscopy exam. During the assesment all singers recorded an excerpt of Aria Non Piu Andrai (The Marriage of Fígaro) by the composer W. A. Mozart. The recording was made through a wavesurfer audio software and analysed by an acoustic analysis program (Praat) This analyses was accomplished in order to verify the presence or absence of the singers formant in the excerpt analysed. At the same time, the singers were submitted to the fibronasalaringoscopy imaging exam in order to obtain the information related to the laryingeal and supralaryingeal adjustments present in the singers formant. Results: All twelve (12) singers avaluated showed laryngeal lowering as the main adjustment. Nine (9) singers presented faryngeal widening as one of the capabilities to realize the singers formant, and seven (7) baritones presented ariepiglotic constriction during utterance os singing voice. Some adjustments not mentioned in literature as ideals for the singers formant were also found in this study. Four singers presented tongue posteriorisation during singing voice; one singer presented, even with tongue posteriorization, a frequency within the average found in this study (3579 Hz). Two (2) singers had associated with tongue posteriorization, a pharyingeal wall constriction, and were the ones who presented the lowest frequencies found (3252 Hz and 3323 Hz). However, one factor that drew in this study was the baritone, whose tongue posteriorization hindered both the mobility and the laryngeal visualization during the avaluated excerpt. This baritone had the highest frequency and the highest intensity found in this study (3944 Hz), with a difference of 400 Hz among the other baritones avaluated. One point worth highlighting and which deserves special attention is that this baritone was the only one afro-brazilian taking part in this research. Conclusions: All the baritones avaluated presented laryingeal lowering as the main capabilities for the singers formant. And nine (9) of them presented the pharyngeal widening as one of the forms to benefit the singers formant. Some adjustments not reported in literature as ideals were found. One example is the pharyngeal constriction and the tongue base posteriorization during singing. We believe that some of these adjustments may be associated with technical properties of singing and/or structural alterations of the vocal tract.